An investigation into Designing Smart city in Accordance with Designing for Children toward Child-Friendly Smart Cities - Rastegar, Amir; Irani, Mazdak; Shojaedingivi, Behzad (International Journal of Scientific Research and Management (IJSRM), 2018)
The process of urban planning should be multi-dimensional and comprehensive meaning that it takes into consideration all groups of people especially less able ones. Children are one of these groups who should be taken into consideration more in urban planning and urban design. Planning to make cities smart is one of the new approaches in urban design. However, children are often largely ignored in these plans. The researchers of the present study tried to examine the position of children in smart city-related planning. To this end, the concepts of child-friendly cities are dealt with and studied so that its common indexes with the smart city would be extracted hoping that the position of children in smart cities would be considered more. The research method employed in the study is library-based and analytic-descriptive.